Context matters: PrEP adherence is associated with sexual behavior among HIV serodiscordant couples in East Africa - Haberer, Jessica E.; Ngure, Kenneth; Muwonge, Timothy; Mugo, Nelly; Katabira, Elly; Heffron, Renee; Musinguzi, Nicholas; Bangsberg, David R.; Celum, Connie; Baeten, Jared M. (Journal of acquired immune deficiency syndromes, 2017)
Short message service (SMS) surveys are a promising tool for understanding whether pre-exposure prophylaxis (PrEP) adherence aligns with risk for HIV acquisition— a concept known as prevention-effective adherence. Methods—The Partners Demonstration Project was an open-label study of integrated PrEP and antiretroviral therapy (ART) delivery among high-risk HIV serodiscordant couples in East Africa. HIV-uninfected partners were offered PrEP until their HIV-infected partner had taken ART for ≥6 months. At 2 study sites, HIV-uninfected partners were offered enrollment into the Partners Mobile Adherence to PrEP (PMAP) sub-study based on ongoing PrEP use, personal cell phone ownership, and ability to use SMS. SMS surveys asked about PrEP adherence and sexual activity in the prior 24 hours; these surveys were sent daily for the 7 days prior and 7 days after routine study visits in the Partners Demonstration Project. Results—The PMAP sub-study enrolled 373 HIV-uninfected partners; 69% were male and mean age was 31 years. Participants completed 17,030 of 23,056 SMS surveys sent (74%) with a mean of 47 surveys per participant over 9.8 months of follow-up. While HIV-infected partner use of ART was <6 months, mean reported PrEP adherence was 92% on surveys concurrently reporting sex within the serodiscordant partnership and 84% on surveys reporting no sex (p<0.001). Discussion—SMS surveys provided daily assessment of concurrent PrEP adherence and sexual behavior. Higher PrEP adherence was temporally associated with increased risk for HIV acquisition.
Keywords: HIV; Pre-exposure prophylaxis (PrEP); SMS; Adherence